Multiculturalism in Island South-East Asian - Chua Beng Huat (Antropologi Indonesia, 2002)
"As postcolonial nations, the boundaries of countries in island Southeast Asia were determined and delineated by the respective colonial administrations prior to political independence. Consequently, the territorial boundaries approximately correspond with the territorial limits under colonial tutelage. Within these territories are to be found indigenous colonized population and resident immigrant populations encouraged by the economic opportunities provided by colonization. As postcolonial nations, these countries are unavoidably 'multiracial' or 'multiethnic', and thus 'multicultural', by their colonial legacies. Each of these countries has transformed this demographic and geographic reality into part of the national ideology and political practice, in respective ways that are historically over determined. This paper will attempt to place these three cases within a larger theoretical framework of multiculturalism and call for political adjustments in the three polities."